Preparation method of hard carbon negative electrode material for long-circulation sodium ion battery
Through the mixing of biomass materials and enzymes, a hard carbon anode material of sodium ion battery with excellent first charge and discharge efficiency and long cycle life was prepared, which solved the short life of existing sodium ion battery anode materials. The problem.
Patent Information
- Application Number
- CN202411263070.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
AI Technical Summary
The negative electrode materials of existing sodium ion batteries have short cycle life, insufficient first charge and discharge efficiency and reversible capacity, and need improvement.
The biomass material and enzyme are mixed with the enzyme and the carbonization process is carried out twice, including the first carbonization and pickling treatment, and then mixed with the pre-sodium agent for the second carbonization to form a hard carbon negative electrode material.
It improves the first charge and discharge efficiency and cycle life of hard carbon negative electrode materials, reduces the consumption of sodium ions and the boiling point of miscellaneous elements, and enhances the disorder and application prospects of the material.
Smart Images

Figure BDA0005036330270000101 
Figure BDA0005036330270000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a hard carbon negative electrode material for a long-cycle sodium ion battery. Background Art
[0002] With the development of clean energy, electrochemical energy storage technology has received extensive attention. Secondary batteries have shown great potential in the fields of energy storage and electric vehicles. However, the negative electrode materials of sodium ion batteries currently have deficiencies in terms of cycle life and other aspects, which urgently need to be improved.
[0003] Hard carbon materials have become one of the preferred negative electrode materials for secondary batteries due to their large carbon layer spacing and abundant active sites. At present, the main process of making hard carbon from biomass materials is to obtain hard carbon that can be used as a secondary negative electrode material by pre-carbonization-crushing-carbonization of biomass raw materials. The current hard carbon negative electrode materials have poor cycle stability and short battery life.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery, which has excellent initial charge and discharge efficiency, reversible capacity and cycle life.
[0006] To achieve the above objectives, in a first aspect of the present application, the present application provides a method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery, comprising the following steps:
[0007] The biomass material and the enzyme are mixed evenly, and allowed to stand for enzymolysis to obtain a mixture;
[0008] Carrying the mixture for the first time to obtain carbide;
[0009] The carbide is crushed to obtain a crushed product, the crushed product is added into a mixed acid solution, and the product is acid-washed, filtered, and dried to obtain a precursor;
[0010] The precursor and the pre-sodiumizing agent are mixed evenly, and a second carbonization is performed to obtain a hard carbon negative electrode material.
[0011] As an embodiment of the present application, the biomass material includes at least one of pine wood powder, lotus powder, and bamboo powder;
[0012] The enzyme comprises at least one of ligninase, laccase and lignin peroxidase.
[0013] As an embodiment of the present application, the mass ratio of the biomass material to the enzyme is (100-300):1.
[0014] As an implementation scheme of the present application, the temperature of the first carbonization is 200-500° C., and the time of the first carbonization is 4-6 hours.
[0015] As an implementation scheme of the present application, the mixed acid solution includes a sulfuric acid solution and a hydrochloric acid solution, the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:(0.5-2); the mass fraction of the sulfuric acid solution is 40-50%, and the mass fraction of the hydrochloric acid solution is 30-37%.
[0016] As an implementation scheme of the present application, the pre-sodium agent includes at least one of sodium phosphite, sodium oxalate, and sodium carbonate; the mass ratio of the pre-sodium agent to the precursor is 1:(500-3000).
[0017] As an embodiment of the present application, the temperature of the second carbonization is 1100-1400° C., and the time of the second carbonization is 1-3 hours.
[0018] According to an embodiment of the present application, the average particle size of the pulverized material is 2 to 10 μm.
[0019] As an embodiment of the present application, the water content of the precursor is 1 to 3%.
[0020] The beneficial effects of the present invention are as follows: the present application creatively mixes biomass materials with enzymes, allows static enzymolysis, effectively degrades lignin, increases the content of cellulose and hemicellulose, and then carbonizes it once, promotes the formation of short-range graphite crystals in the subsequent carbonization process, increases the disorder inside the hard carbon negative electrode material, and then undergoes acid washing and pre-sodium treatment to reduce the consumption of sodium ions in the electrolyte when the hard carbon negative electrode material contacts the electrolyte, reduces the boiling point of the impurity elements, and makes the surface defects of the carbonized material fewer, effectively improves the initial charge and discharge efficiency of the hard carbon negative electrode material, and increases the reversible capacity and cycle life, and has broad application prospects. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0022] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0023] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0024] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0025] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.
[0026] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0027] The present invention provides a method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery, comprising the following steps:
[0028] The biomass material and the enzyme are mixed evenly, and allowed to stand for enzymolysis to obtain a mixture;
[0029] Carrying the mixture for the first time to obtain carbide;
[0030] The carbide is crushed to obtain a crushed product, the crushed product is added to a mixed acid solution, stirred evenly, and dried to obtain a precursor;
[0031] The precursor and the pre-sodiumizing agent are mixed evenly, and a second carbonization is performed to obtain a hard carbon negative electrode material.
[0032] The present application creatively mixes biomass materials with enzymes (similar to the principle of fermentation, without the need for enzymatic hydrolysis in water), allows static enzymatic hydrolysis, effectively degrades lignin, increases the content of cellulose and hemicellulose, and then carbonizes it once to promote the formation of short-range graphite crystals in the subsequent carbonization process, thereby increasing the degree of disorder inside the hard carbon negative electrode material. It is then acid-washed and pre-sodiumized to reduce the consumption of sodium ions in the electrolyte when the hard carbon negative electrode material is in contact with the electrolyte, thereby reducing the boiling point of the impurity elements, and making the surface defects of the carbonized material fewer, thereby effectively improving the initial charge and discharge efficiency of the hard carbon negative electrode material, and increasing the reversible capacity and cycle life, and has broad application prospects.
[0033] In one embodiment, the biomass material includes at least one of pine wood powder, lotus powder, and bamboo powder;
[0034] The enzyme includes at least one of ligninase, laccase, and lignin peroxidase. The inventors of the present application have found that the type of enzyme is one of the key factors in achieving the effect of the present application. When at least one of ligninase, laccase, and lignin peroxidase is used, lignin can be better degraded, the content of cellulose and hemicellulose can be increased, and the formation of short-range graphite crystals in the subsequent carbonization process can be effectively promoted, and the disorder inside the hard carbon negative electrode material can be increased, thereby better improving the initial charge and discharge efficiency, reversible capacity and cycle life.
[0035] In one embodiment, the mesh size of the biomass material is 50-200 meshes.
[0036] The lotus seed pod powder is obtained by crushing the lotus seed pod, the pine wood powder is obtained by crushing the pine wood, and the bamboo powder is obtained by crushing the bamboo.
[0037] In one embodiment, the mass ratio of the biomass material to the enzyme is (100-300):1, for example, it can be 100:1, 120:1, 150:1, 180:1, 200:1, 220:1, 250:1, 280:1, 300:1 or a range consisting of any two of the values.
[0038] In one embodiment, the temperature of the first carbonization is 200-500°C, for example, it can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two of these values. The inventors of the present application have found that the carbonization temperature has a great influence on the performance of the hard carbon negative electrode material. By controlling the temperature to carbonize within this range, the pore plasticity of the hard carbon negative electrode material is good, and short-range graphite crystals can be effectively formed, thereby increasing the disorder inside the hard carbon negative electrode material. If the temperature is too low (below 200°C), the carbonization effect cannot be achieved, resulting in excessive volatiles in the subsequent second carbonization. If the temperature is too high, the pore plasticity of the material is poor, and it is difficult to form short-range graphite crystals.
[0039] In one embodiment, the first carbonization time is 4 to 6 hours, for example, 4 hours, 4.2 hours, 4.5 hours, 4.8 hours, 5 hours, 5.2 hours, 5.5 hours, 5.8 hours, 6 hours or a range consisting of any two values therein.
[0040] In one embodiment, the first carbonization is performed under an inert atmosphere.
[0041] In one embodiment, the inert atmosphere includes at least one of nitrogen, argon, and helium.
[0042] In one embodiment, the mixed acid solution includes a sulfuric acid solution and a hydrochloric acid solution, and the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:(0.5-2), for example, it can be 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2 or a range consisting of any two of the values.
[0043] In one embodiment, the mass fraction of the sulfuric acid solution is 40-50%, for example, it can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or a range consisting of any two values therein.
[0044] In one embodiment, the mass fraction of the hydrochloric acid solution is 30-37%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37% or a range consisting of any two values therein.
[0045] In one embodiment, the pre-sodium agent includes at least one of sodium phosphite, sodium oxalate, and sodium carbonate; the mass ratio of the pre-sodium agent to the precursor is 1:(500-3000), for example, it can be 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000, 1:1200, 1:1500, 1:1800, 1:2000, 1:3000 or a range consisting of any two of the values.
[0046] In one embodiment, the pre-sodium agent includes at least one of sodium phosphite, sodium oxalate, and sodium carbonate; the mass ratio of the pre-sodium agent to the precursor is 1:(1000-2000).
[0047] In one embodiment, the temperature of the second carbonization is 1100-1400°C, for example, it can be 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C or a range consisting of any two of these values.
[0048] In one embodiment, the second carbonization time is 1 to 3 hours, for example, 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours or a range consisting of any two values therein.
[0049] In one embodiment, the second carbonization is performed in an environment with a relative vacuum degree of -10 to -100 Pa.
[0050] In one embodiment, the average particle size of the pulverized material is 2 to 10 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range consisting of any two of these values.
[0051] In one embodiment, the carbide is crushed by a crushing device, and the crushing device includes at least one of a jet mill, a mechanical mill, and a roller mill.
[0052] In one embodiment, the water content of the precursor is 1-3%, for example, it can be 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two values therein.
[0053] In one embodiment, the drying adopts rotary evaporation, hot air, flash evaporation and other methods to control the moisture content below 3%.
[0054] In one embodiment, the static enzymatic hydrolysis time is 24 to 48 hours, for example, it can be 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 hours or a range consisting of any two values therein.
[0055] The present application is further described below with specific embodiments:
[0056] Example 1
[0057] A method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery comprises the following steps:
[0058] (1) 100-mesh lotus seed powder and laccase were mixed evenly in a mass ratio of 100:1, and allowed to stand for enzymolysis for 36 hours to obtain a mixture;
[0059] (2) placing the mixture in a heating device and carbonizing it at 200° C. for 4 h under the protection of an inert gas to obtain a carbide;
[0060] (3) The carbide was ground into an average particle size of 5 μm using a jet mill, and the ground material was added to a mixed acid solution, stirred at 100° C. and 300 rpm for 5 h, and rotary evaporated until the water content was 3%, thereby obtaining a precursor;
[0061] The mass ratio of the crushed material to the mixed acid solution is 1:10;
[0062] The mixed acid solution comprises a sulfuric acid solution and a hydrochloric acid solution, the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:1; the mass fraction of the sulfuric acid solution is 45%, and the mass fraction of the hydrochloric acid solution is 37%.
[0063] (4) The precursor and sodium phosphite were mixed evenly in a mass ratio of 2000:1, the mixed sample was placed in a vacuum furnace, and vacuum carbonized at -10 Pa and 1400° C. for 4 h to obtain a hard carbon negative electrode material.
[0064] Example 2
[0065] The difference between Example 2 and Example 1 is that the mass ratio of lotus seed powder to laccase in Example 2 is 200:1, and other conditions are the same.
[0066] Example 3
[0067] The difference between Example 3 and Example 1 is that the mass ratio of lotus seed powder to laccase in Example 3 is 300:1, and other conditions are the same.
[0068] Example 4
[0069] The difference between Example 4 and Example 1 is that the mass ratio of lotus seed powder to laccase in Example 4 is 500:1, and other conditions are the same.
[0070] Example 5
[0071] The difference between Example 5 and Example 1 is that the carbonization temperature of step (2) of Example 5 is 500° C. (ie, the primary carbonization temperature of this example is 500° C.), and the other conditions are the same.
[0072] Example 6
[0073] The difference between Example 6 and Example 1 is that the ratio of precursor to sodium phosphite is 500:1, and other conditions are the same.
[0074] Example 7
[0075] The difference between Example 7 and Example 1 is that the ratio of precursor to sodium phosphite is 1000:1, and other conditions are the same.
[0076] Example 8
[0077] The difference between Example 8 and Example 1 is that the ratio of precursor to sodium phosphite is 3000:1, and other conditions are the same.
[0078] Example 9
[0079] The difference between Example 9 and Example 1 is that Example 9 uses an equal amount of sodium oxalate to replace sodium phosphite, and other conditions are the same.
[0080] Example 10
[0081] The difference between Example 10 and Example 1 is that Example 10 uses an equal amount of sodium carbonate to replace sodium phosphite, and other conditions are the same.
[0082] Embodiment 11
[0083] The difference between Example 11 and Example 1 is that the vacuum degree of step (4) of Example 11 is -50Pa, and the others are the same.
[0084] Example 12
[0085] The difference between Example 12 and Example 1 is that the vacuum degree of step (4) of Example 12 is -50Pa, and the others are the same.
[0086] Embodiment 13
[0087] The difference between Example 13 and Example 1 is that the carbonization temperature of step (4) of Example 13 is 1100°C (ie, the secondary carbonization temperature of this example is 1100°C), and other conditions are the same.
[0088] Embodiment 14
[0089] The difference between Example 14 and Example 1 is that Example 14 uses an equal amount of ligninase to replace laccase, and other conditions are the same.
[0090] Embodiment 15
[0091] The difference between Example 15 and Example 1 is that Example 15 uses an equal amount of lignin peroxidase to replace laccase, and other conditions are the same.
[0092] Example 16
[0093] The difference between Example 16 and Example 1 is that Example 16 uses pine wood powder of equal particle size and equal amount to replace lotus seed powder, and other conditions are the same.
[0094] Embodiment 17
[0095] The difference between Example 17 and Example 1 is that Example 17 uses bamboo powder of equal particle size and equal amount to replace lotus seed pod powder, and other conditions are the same.
[0096] Comparative Example 1
[0097] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 is not subjected to enzymatic hydrolysis, and other conditions are the same.
[0098] A method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery comprises the following steps:
[0099] (1) placing lotus seed powder of 100 meshes in a heating device and carbonizing it at 200° C. for 4 h under the protection of an inert gas to obtain a carbide;
[0100] (2) The carbide was ground into an average particle size of 5 μm using a jet mill, and the ground material was added to a mixed acid solution, stirred at 100° C. and 300 rpm for 5 h, and rotary evaporated until the water content was 3%, thereby obtaining a precursor;
[0101] The mass ratio of the crushed material to the mixed acid solution is 1:10;
[0102] The mixed acid solution comprises a sulfuric acid solution and a hydrochloric acid solution, the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:1; the mass fraction of the sulfuric acid solution is 45%, and the mass fraction of the hydrochloric acid solution is 37%.
[0103] (3) The precursor and sodium phosphite were mixed evenly in a mass ratio of 2000:1, the mixed sample was placed in a vacuum furnace, and vacuum carbonized at -10 Pa and 1400° C. for 4 h to obtain a hard carbon negative electrode material.
[0104] Comparative Example 2
[0105] The difference between Example 2 and Example 1 is that Example 2 is not subjected to a carbonization, and other conditions are the same.
[0106] A method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery comprises the following steps:
[0107] (1) 100-mesh lotus seed powder and laccase were mixed evenly in a mass ratio of 100:1, and allowed to stand for enzymolysis for 36 hours to obtain a mixture;
[0108] (2) The mixture was ground into an average particle size of 5 μm using a jet mill, the ground material was added to a mixed acid solution, stirred at 100° C. and 300 rpm for 5 h, and rotary evaporated until the water content was 3%, thereby obtaining a precursor;
[0109] The mass ratio of the crushed material to the mixed acid solution is 1:10;
[0110] The mixed acid solution comprises a sulfuric acid solution and a hydrochloric acid solution, the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:1; the mass fraction of the sulfuric acid solution is 45%, and the mass fraction of the hydrochloric acid solution is 37%.
[0111] (3) The precursor and sodium phosphite were mixed evenly in a mass ratio of 2000:1, the mixed sample was placed in a vacuum furnace, and vacuum carbonized at -10 Pa and 1400° C. for 4 h to obtain a hard carbon negative electrode material.
[0112] Comparative Example 3
[0113] The difference between Comparative Example 3 and Example 1 is that the carbonization temperature of step (2) of Comparative Example 3 is 900° C., that is, the primary carbonization temperature of this comparative example is 900° C.), and the other conditions are the same.
[0114] Comparative Example 4
[0115] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 is not sodiumized, and other conditions are the same.
[0116] A method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery comprises the following steps:
[0117] (1) 100-mesh lotus seed powder and laccase were mixed evenly in a mass ratio of 100:1, and allowed to stand for enzymolysis for 36 hours to obtain a mixture;
[0118] (2) placing the mixture in a heating device and carbonizing it at 200° C. for 4 h under the protection of an inert gas to obtain a carbide;
[0119] (3) The carbide was ground into an average particle size of 5 μm using a jet mill, and the ground material was added to a mixed acid solution, stirred at 100° C. and 300 rpm for 5 h, and rotary evaporated until the water content was 3%, thereby obtaining a precursor;
[0120] The mass ratio of the crushed material to the mixed acid solution is 1:10;
[0121] The mixed acid solution comprises a sulfuric acid solution and a hydrochloric acid solution, the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:1; the mass fraction of the sulfuric acid solution is 45%, and the mass fraction of the hydrochloric acid solution is 37%.
[0122] (4) The precursor is vacuum carbonized at -10 Pa and 1400°C for 4 h to obtain a hard carbon negative electrode material.
[0123] Comparative Example 5
[0124] The difference between Comparative Example 5 and Example 1 is that the carbonization temperature of step (4) of Comparative Example 5 is 900° C. (ie, the secondary carbonization temperature of this comparative example is 1400° C.), and other conditions are the same.
[0125] Comparative Example 6
[0126] The difference between Comparative Example 6 and Example 1 is that the carbonization temperature of step (4) of Comparative Example 6 is 1800° C. (ie, the secondary carbonization temperature of this comparative example is 1400° C.), and other conditions are the same.
[0127] Performance Testing
[0128] Preparation of secondary battery: Prepare polyvinylidene fluoride solution with mass fraction of 6-7% by N-methylpyrrolidone as solvent, mix hard carbon negative electrode material, polyvinylidene fluoride, conductive carbon black and polyvinylidene fluoride solution in mass ratio of 90:5:5, apply on copper foil, put the coated electrode into vacuum drying oven at temperature of 110℃ for 4 hours, cut into small discs with diameter of 14cm. Then transfer to German Mikaelona glove box filled with argon gas to assemble 2430 button cells, use 1mol / L LiPF6 three-component mixed solvent according to EC:DMC:EMC=1:1:1 (volume ratio) as electrolyte, metal sodium sheet as counter electrode, 16μm thick Ube diaphragm as isolation membrane, and conduct electrochemical performance test on assembled half-cell on American Arbin electrochemical detection system, charge and discharge voltage range is 0V to 2.0V, rate is 0.1C, cycle test rate is 1C.
[0129] Table 1
[0130]
[0131]
[0132] It can be seen from Table 1 that the negative electrode hard carbon material of the present invention has excellent first charge and discharge efficiency, reversible capacity and cycle life.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery, characterized in that: The following steps are involved: The biomass material and the enzyme are mixed evenly, and allowed to stand for enzymolysis to obtain a mixture; Carrying the mixture for the first time to obtain carbide; The carbide is crushed to obtain a crushed product, the crushed product is added into a mixed acid solution, and the product is acid-washed, filtered, and dried to obtain a precursor; The precursor and the pre-sodiumizing agent are mixed evenly, and a second carbonization is performed to obtain a hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The biomass material includes at least one of pine wood powder, lotus powder and bamboo powder.
3. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The enzyme comprises at least one of ligninase, laccase and lignin peroxidase.
4. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The mass ratio of the biomass material to the enzyme is (100-300):
1.
5. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The temperature of the first carbonization is 200-500° C., and the time of the first carbonization is 4-6 hours.
6. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The mixed acid solution comprises a sulfuric acid solution and a hydrochloric acid solution, the mass ratio of the sulfuric acid solution to the hydrochloric acid solution is 1:(0.5-2); the mass fraction of the sulfuric acid solution is 40-50%, and the mass fraction of the hydrochloric acid solution is 30-37%.
7. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The pre-sodiumization agent includes at least one of sodium phosphite, sodium oxalate and sodium carbonate; the mass ratio of the pre-sodiumization agent to the precursor is 1:(500-3000).
8. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The temperature of the second carbonization is 1100-1400° C., and the time of the second carbonization is 1-3 hours.
9. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The average particle size of the pulverized product is 2 to 10 μm.
10. The method for preparing a hard carbon negative electrode material for a long cycle sodium ion battery according to claim 1, characterized in that: The water content of the precursor is 1-3%.
Citation Information
Cited By
Preparation method of sodium electric hard carbon material
CN120622466A
